Effects of prey quality and predator body size on prey DNA detection success in a centipede predator. Issue 15 (3rd February 2014) - Eitzinger, B.; Unger, E. M.; Traugott, M.; Scheu, S.
Abstract Predator body size and prey quality are important factors driving prey choice and consumption rates. Both factors might affect prey detection success in PCR‐based gut content analysis, potentially resulting in over‐ or underestimation of feeding rates. Experimental evidence, however, is scarce. We examined how body size and prey quality affect prey DNA detection success in centipede predators. Due to metabolic rates increasing with body size, we hypothesized that prey DNA detection intervals will be shorter in large predators than in smaller ones. Moreover, we hypothesized that prey detection intervals of high‐quality prey, defined by low carbon‐to‐nitrogen ratio will be shorter than in low‐quality prey due to faster assimilation. Small, medium and large individuals of centipedes Lithobius spp. (Lithobiidae, Chilopoda) were fed Collembola and allowed to digest prey for up to 168 h post‐feeding. To test our second hypothesis, medium‐sized lithobiids were fed with either Diptera or Lumbricidae. No significant differences in 50% prey DNA detection success time intervals for a 272‐bp prey DNA fragment were found between the predator size groups, indicating that body size does not affect prey DNA detection success. Post‐feeding detection intervals were significantly shorter in Lumbricidae and Diptera compared to Collembola prey, apparently supporting the second hypothesis. However, sensitivity of diagnostic PCR differed between prey types, and quantitative PCR revealed that concentration of targeted DNA varied significantly between prey types. This suggests that both DNA concentration and assay sensitivity need to be considered when assessing prey quality effects on prey DNA detection success.